A comparative analysis of patent law for software related invention in Malaysia and European Union / Abdul Qayyum Zulfadhli Zulkiflee - Zulkiflee, Abdul Qayyum Zulfadhli (2013)
In this study, the main objective of the writer has been to examine and compare the patent laws for software related inventions in the European Union and Malaysia. To this extent, the writer hopes that this study has at least been a partial success and may lead to a better understanding of the processes, legal stand and instances for the patentability of software related inventions. The general rule concerning the patentability of software or computer programme has been laid down in Section 52 of the European Patent Convention 1873 and Section 13 of the Malaysian Patent Act 1983 (Act 291). Although these provisions expressly exclude software or computer programmes from patentability, there are some instances where patents for this subject matter are granted. Indeed, the writer himself has benefited immensely from this study. The writer would at this stage like to take the opportunity to record his gratitude and appreciation to the staffs of the Malaysian Intellectual Property Organisation and the Malaysian Institute of Microelectronic Systems who had kindly consented to give interviews and to relate their experiences on the Field; not to forget all others who have helped in one way or another in the course of this study.